2008
DOI: 10.1007/s11199-008-9519-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of “Good Mother” Stereotypes in the College Environment

Abstract: This study extends research on the good mother stereotype by examining students' perceptions of other students who return to school after having a child. Undergraduate students attending either community college or a 4-year southeastern university within the United States were asked to review a vignette in which a mother's decision to return to college and her role satisfaction were manipulated. The 205 participants rated the woman who elects to continue her education shortly after the birth of a child as sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Male participants also had less favorable impressions of a stay-at-home father than of a working or leave-taking father, although this difference did not achieve significance. These results suggest that men's support for traditional gender roles, particularly those that involve work and family choices, may be stronger than women's, a finding that is supported by other literature on attitudes toward gender roles (e.g., Kaufman 2000; Larsen and Long 1988) and attitudes toward mothers specifically (Mottarella et al 2009). …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Male participants also had less favorable impressions of a stay-at-home father than of a working or leave-taking father, although this difference did not achieve significance. These results suggest that men's support for traditional gender roles, particularly those that involve work and family choices, may be stronger than women's, a finding that is supported by other literature on attitudes toward gender roles (e.g., Kaufman 2000; Larsen and Long 1988) and attitudes toward mothers specifically (Mottarella et al 2009). …”
Section: Discussionsupporting
confidence: 72%
“…Further, Bridges and colleagues found that working mothers were viewed as less communal than mothers who stopped working and mothers who took a short maternity leave following the birth of their child (Bridges and Orza 1993;Bridges and Etaugh 1995). Similarly, Mottarella et al (2009) found that mothers who chose to return to school immediately after the birth of a child were judged as less warm than mothers who chose to discontinue their schooling. Studying perceptions of mothers and fathers, Fuegen et al (2004) found that working parents were viewed as less agentic and committed to their jobs than working non-parents.…”
Section: Perceptions Of Working and Stay-at-home Parentsmentioning
confidence: 99%
“…Between 2000 and 2012, the enrollment of students aged 25 years and older increased by 35%, and projections estimate that from 2012 to 2023, there will be another 20% increase in enrollment among this age group . In fact, female students over the age of 25 are the fastest‐growing group of nontraditional students in US colleges and universities . This is particularly noteworthy, given that the average age of women at first birth (and thus with the decision to breastfeed) has been increasing over time, from 22.7 years in 1980 to 25.8 years in 2012…”
Section: Discussionmentioning
confidence: 99%
“…The following quotation illustrated this sub-theme: "[Single mothers] will give up a lot for their children." Thus, this culturally prescribed idea of being self-sacrificing aligns with the "good mother" stereotype, which lends to the proposal that once a woman becomes a mother, any former identity is no longer relevant and her individual needs should be ignored (Mottarella et al, 2009). …”
Section: Single Mothers and Fathers Provide Differently For Their Chimentioning
confidence: 97%
“…The few studies that exist appear to highlight the "good mother" stereotype, which involves the culturally prescribed belief that in order to be successful in the role of a mother, a woman must only spend time with her children and put others' needs ahead of her own (Mottarella, Fritzsche, Whitten, & Bedsole, 2009). For example, Brodsky (1996) studied single mothers raising their children in an inner-city neighborhood, all of whom were identified as resilient by school personnel because of their abilities to thrive and raise children in difficult circumstances; however, this study did not identify any specific positive attributes beyond surviving and thriving.…”
Section: The Perceived Positive Attributes Of Single Mothers and Fathersmentioning
confidence: 99%